2021
DOI: 10.3390/jrfm14060253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Unconventional Monetary Policy of the Bank of Japan: A DSGE Approach

Abstract: When the nominal interest rate reaches the zero lower bound (ZLB), a conventional monetary policy, namely, the adjustment of short-term interest rate, may become impractical and ineffective for central banks. Therefore, quantitative easing (QE) is one of the few available policy options of central banks for stimulating the economy and dealing with deflationary pressure. Since February 1999, the Bank of Japan (BoJ) has conducted several unconventional monetary policy programs. Considering the scarce research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The traditional literature for QE is generally focused on the impacts to infation and output because these are the most important measures for successful monetary policy. This traditional literature provides compelling evidence that QE in Japan successfully increased the level of infation, but the impacts to economic growth are not statistically signifcant (Wang 2021). Although QE increased the level of infation in Japan, as measured by the year-over-year consumer price index (CPI), the BOJ was not able to reach its target for infation (Statistics Bureau 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional literature for QE is generally focused on the impacts to infation and output because these are the most important measures for successful monetary policy. This traditional literature provides compelling evidence that QE in Japan successfully increased the level of infation, but the impacts to economic growth are not statistically signifcant (Wang 2021). Although QE increased the level of infation in Japan, as measured by the year-over-year consumer price index (CPI), the BOJ was not able to reach its target for infation (Statistics Bureau 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang [62] stated that if monetary policymakers want to reduce inflation at the macroeconomic level, they should use a quantitative easing policy. The authors of this study presented a DSGE model using the economic data of Japan from 2013 based on government bonds with different maturities, and they analyzed the relationship between the behavior of the Bank of Japan and the implementation of a policy of quantitative easing with inflation and interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, the experiences gained at first can be considered to be changes in the effectiveness of monetary policy, but the fact is that the lack of attention to non-neoclassical channels has led to this. Recent studies show that different countries have seen different results from the impact of policies and monetary shocks on the real sectors of the economy due to the different characteristics of banks and firms, and factors such as the balance sheet and financial health of banks play a different role in the impact of monetary policy [10,59,62,64,[97][98][99][100].…”
Section: Introductionmentioning
confidence: 99%
“…In a research, Wang [ 31 ] has stated that if monetary policymakers want to reduce inflation at the macroeconomic level, they should use quantitative easing policy. The authors of this study have presented a DSGE model using the economic data of Japan in 2013 based on government bonds with different maturities and they have tried to analyze the relationship between the behavior of the Bank of Japan and the implementation of a policy of quantitative easing with inflation and interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the growing importance of financial markets both at the national and international levels and the effectiveness of such markets in terms of monetary policies, the effectiveness of monetary policies through its various mechanisms has been researched more than before. For example, the global financial crisis in recent years and the measures taken by the Central Bank of Europe and the United States to solve it, or the use of quantitative easing policies, showed that the importance of monetary policies and its effectiveness on all types of markets and the realization of economic growth and inflation control is undeniable [27][28][29][30][31][32][33]. Secondly, it is necessary to pay attention to the mechanisms and channels of monetary transmission in order to make policies more effective [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%